Microlite offered free-choice to growing-finishing pigs - Koch, B.A.; Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Growing and finishing pigs consumed from 54 to 64 grams of Microlite per head per day when it was available free choice from a self-feeder. It had no measurable affect on average daily gain, feed consumption, feed efficiency, or behavior of pigs eating a complete ration.
Swine Industry Day 1975 is known as Swine Day, 1975
Keywords: Swine; Microlite; Growing pigs; Finishing pigs